Predictors of bank distress: The 1907 crisis in Sweden - Anna Grodecka; Sean Kenny; Anders Ögren (Sveriges Riksbank, 2018)
This paper contributes to literature on bank distress using the Swedish experience of the international crisis of 1907, often paralleled with 2008. By employing previously unanalyzed bank-level data, we use logit regressions and principal component analysis to measure the impact of pre-crisis bank characteristics on the probability of their subsequent distress. The crisis was characterized by "creative destruction", as those banks with weaker corporate governance structures, wider branching networks, operating with lower cost efficiency were more likely to experience distress. We find that poor credit allocation rather than foreign borrowing, as often stressed, were associated with ultimate demise.
Keywords: E58; G21; G28; H12; N23; 330; Bank Distress; Financial Crises; Swedish Banks; Lender of Last Resort